1984
DOI: 10.1302/0301-620x.66b4.6746688
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic arthroscopy of the knee in children

Abstract: Seventy-two symptomatic knees were studied in 68 patients between 2 and 17 years of age. A firm clinical diagnosis was made in all knees before arthroscopy. The clinical diagnosis and the arthroscopic findings were compared to establish the accuracy of the clinical diagnosis. This was 42% in children under 13 years old (Group 1) and 55% in children between 14 and 17 (Group 2). Possible unnecessary arthrotomy was avoided in 58% of the knees in Group 1, and 31% of the knees in Group 2. The most common "incorrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0
3

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 3 publications
5
12
0
3
Order By: Relevance
“…Albeit uncertain, clinical diagnosis is better in adults ( et al , Suman et al 1984. The diagnostic accuracy improved more in our youngest age group, confirming Morrisy et al (1982) and the tendency illustrated by Suman et al (1984).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Albeit uncertain, clinical diagnosis is better in adults ( et al , Suman et al 1984. The diagnostic accuracy improved more in our youngest age group, confirming Morrisy et al (1982) and the tendency illustrated by Suman et al (1984).…”
Section: Discussionsupporting
confidence: 76%
“…Albeit uncertain, clinical diagnosis is better in adults ( et al , Suman et al 1984. The diagnostic accuracy improved more in our youngest age group, confirming Morrisy et al (1982) and the tendency illustrated by Suman et al (1984). The communication barrier between child and doctor certainly increases with decreasing age of the child, and this might explain the abovementioned difference between the two agegroups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Morrissy et al 14 reported that arthroscopic examination confirmed the clinical diagnosis in 13 (62%) of 21 patients between 13 and 18 years, but in only 3 (27%) of 11 patients younger than 13 years. Suman et al 23 reported that arthroscopic examination avoided unnecessary arthrotomy in 31% of children between 14 and 17 years and in 58% of those younger than 13 years. We agree with these authors, and we repaired osteochondral defects and removed intraarticular loose bodies without having to perform an arthrotomy in any patient.…”
Section: Resultsmentioning
confidence: 99%
“…Few reports have attempted to evaluate the cause of an acute traumatic hemarthrosis of the knee in a child.2, 6, ~, 9, 22 When a child sustains a severe injury to the knee, unlike an adult, he or she will often not remember the exact mechanism of injury, making the evaluation more difficult. Suman et al 23 compared the findings at arthroscopic evaluation with their preoperative clinical diagnosis in 68 patients in whom 72 knees were examined. They reported that the clinical diagnosis was accurate in only 8 (42%) of 19 knees in children under 13 years and in 27 (56%) of 48 knees in adolescents between 14 and 17 years.…”
mentioning
confidence: 99%